Intra-Arab Trade : Is it too Little? - Yousef, Tarik (IMF Working Papers; Working Paper ;, 2000)
This paper estimates a gravity model to address the issue of whether intra-Arab trade is too little. Although gravity models have been extensively used to measure bilateral trade among countries, they have-to the best of our knowledge-never been used to measure intra-Arab trade. Our results suggest that intra-Arab trade and Arab trade with the rest of the world are lower than what would be predicted by the gravity equation, suggesting considerable scope for regional-as well as multilateral-integration. The results also suggest that intra-GCC and intra-Maghreb trade are relatively low while the Mashreq countries exhibit a higher level of intragroup trade.